2010
DOI: 10.1086/657320
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis Assessed by Gram Stain and Diminished Colonization Resistance to Incident Gonococcal, Chlamydial, and Trichomonal Genital Infection

Abstract: Background We sought to assess the relationship between bacterial vaginosis (BV) assessed by Gram stain and incident trichomonal (TV), gonococcal (GC) and/or chlamydial (CT) genital infection. Methods 3,620 non-pregnant women aged 15-44 presenting for routine care at 12 clinics in Birmingham, Alabama participated in a longitudinal study. Participants were assessed quarterly for one year. Vaginal smears were categorized by Nugent's Gram stain score (0-3 designated normal, 4-6 intermediate state, 7-10 BV). Poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
286
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(308 citation statements)
references
References 50 publications
12
286
1
9
Order By: Relevance
“…[63][64][65][66] However, we observed that a higher severity of trichomoniasis was associated with lower severity of BV (but higher quantity of Lactobacillus) during pregnancy. To our knowledge, this has not been previously reported, and suggests that Lactobacillus may not be protective against trichomoniasis during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66] However, we observed that a higher severity of trichomoniasis was associated with lower severity of BV (but higher quantity of Lactobacillus) during pregnancy. To our knowledge, this has not been previously reported, and suggests that Lactobacillus may not be protective against trichomoniasis during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There is an evidence that BV, whether it is asymptomatic or symptomatic, is an independent risk factor for severe reproductive tract and obstetric sequelae, including pre-term delivery, pre-term labor, low birth weight, post abortion endometritis, post-partum endometritis [5], development of Pelvic inflammatory disease (PID) as reported by [6], acquisition of sexually transmitted diseases (STIs) as proved by [7], acquisition and transmission of HIV [8]. Due to these serious complications, there has been an increase of interest in bacterial vaginosis during the last decade, regarding its diagnosis and treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…It's estimated that more than 36 million adults are infected with sexually transmitted infections (STIs), especially gonorrhoea, syphilis, trichomoniasis, chlamydia and genital herpes [1,2]. Bacterial vaginosis (BV) is the most common cause of abnormal vaginal discharge among women of childbearing age and is associated with low birth weight infants and preventable preterm births [3,4]. Some studies have found a relationship between BV and high-risk behaviors associated with sexually transmitted infections (STIs) such as early sexual debut and multiple sex partners [5,6].…”
Section: Introductionmentioning
confidence: 99%